The comparison of distress tolerance and experiential avoidance in people with health anxiety and normal people - Moghbeli-Hanzaii M; Omidi A; Zanjani Z (Fiyz̤, 2020)
Background: People with health anxiety experience high levels of concern about physical symptoms and use coping strategies such as avoidance in the face of these negative emotions. This study aimed to compare distress tolerance and experiential avoidance in people with and without health anxiety. Materials and Methods: This is a Case-control study. The research sample consisted of two groups of 40 students from Kashan University and Kashan University of Medical Sciences. The health anxiety group was selected by purposeful sampling. The normal group was selected by convenience sampling method. The research tools were: Short form health anxiety questionnaire (F-SHAI), Distress Tolerance Scale (DTS) and Acceptance and Action Questionnaire-2 (AAQ-2). Data was analyzed using SPSS-19 software and independent t-test. Results: Score mean of experiential avoidance was 28.30 (SD=7.41) in people with health anxiety and 20.15 (SD=7.70) in normal people. The score mean of distress tolerance in people with health anxiety was 38/35 (SD=7.26) and in normal people was 44/42(SD=9.70). The results of Independent t-test showed that there was a significant difference between two groups in experiential avoidance score (t=4.82) and distress tolerance score (t=-3.16, P<0.001). Conclusion: Individuals with health anxiety reported more experiential avoidance and less distress tolerance than normal people. These people are more attracted to their health-related negative emotions and because of the inability to tolerate these distresses, they avoid stressful situations associated with these distresses.